Factors associated to breastfeeding in the first hour of life: systematic review - Esteves, Tania Maria Brasil; Daumas, Regina Paiva; Oliveira, Maria Inês Couto de; Andrade, Carlos Augusto de Ferreira de; Leite, Iuri Costa (Revista de Saúde Pública, 2014)
OBJECTIVE To identify independent risk factors for non-breastfeeding within the first hour of life. METHODS A systematic review of Medline, LILACS, Scopus, and Web of Science electronic databases, till August 30, 2013, was performed without restrictions on language or date of publishing. Studies that used regression models and provided adjusted measures of association were included. Studies in which the regression model was not specified or those based on specific populations regarding age or the presence of morbidities were excluded. RESULTS The search resulted in 155 articles, from which 18 met the inclusion criteria. These were conducted in Asia (9), Africa (5), and South America (4), between 1999 and 2013. The prevalence of breastfeeding within the first hour of life ranged from 11.4%, in a province of Saudi Arabia, to 83.3% in Sri Lanka. Cesarean delivery was the most consistent risk factor for non-breastfeeding within the first hour of life. “Low family income”, “maternal age less than 25 years”, “low maternal education”, “no prenatal visit”, “home delivery”, “no prenatal guidance on breastfeeding” and “preterm birth” were reported as risk factors in at least two studies. CONCLUSIONS Besides the hospital routines, indicators for low socioeconomic status and poor access to health services were also identified as independent risk factors for non-breastfeeding within the first hour of life. Policies to promote breastfeeding, appropriate to each context, should aim to reduce inequalities in health.